IMPLEMENTASI KEBIJAKAN PEMENUHAN HAK ORANG DENGAN GANGGUAN JIWA DI KABUPATEN HULU SUNGAI UTARA - Affrian, Reno (PPPM STIA Amuntai, 2019)
Mental disorders are a collection of abnormal conditions, both those related to physical and mental. Local governments are responsible for fulfilling the rights of people with mental disorders, the right to get treatment and care and rehabilitation in order to obtain complete recovery. Based on the results of the research that has been carried out it can be concluded that: Implementation of the fulfillment of the rights of people with mental disorders has not fully gone well, it is seen from the resources to run mental health services are not fully adequate, and there are still problems related to the economic, social and political. Factors that influence the Implementation of the Fulfillment of the Rights of People with Mental Disorders in Hulu Sungai Utara Regency are influenced by several factors 1. Resources 2. Economic, Social and Political Environment